Calculation of a Health Index of Oil-Paper Transformers Insulation with Binary Logistic Regression. (15th June 2016) - Zuo, Weijie; Yuan, Haiwen; Shang, Yuwei; Liu, Yingyi; Chen, Tao
Abstract : This paper presents a new method for calculating the insulation health index (HI) of oil-paper transformers rated under 110 kV to provide a snapshot of health condition using binary logistic regression. Oil breakdown voltage (BDV), total acidity of oil, 2-Furfuraldehyde content, and dissolved gas analysis (DGA) are singled out in this method as the input data for determining HI. A sample of transformers is used to test the proposed method. The results are compared with the results calculated for the same set of transformers using fuzzy logic. The comparison results show that the proposed method is reliable and effective in evaluating transformer health condition.